Research of a Novel Jumping Robot - Song Yajie; Wu Dong (Jixie chuandong)
A four-bar linkage mechanism is designed based on the leg structure of the kangaroo. The four links are deformed by cam to stretch the spring to store the elastic potential energy. The sudden change of the cam stroke causes the tension spring to release the energy to jump. The experimental prototype is designed based on the mechanism principle. The simulation experiment is carried out by analysis software Adams, and the experimental prototype is verified experimentally. The experimental jump height is up to twice the length, elastic potential energy utilization rate of 70%. The correctness and rationality of the design and theoretical analysis of the four-bar linkage mechanism are verified by the result, then the main influencing factors that affect the jumping ability are analyzed, the conclusion is obtained and the improvement scheme is given.